An Amino Acid Polymorphism in Histidine-rich Glycoprotein (HRG) Explains 59% of the Variance in Plasma HRG Levels - Hennis, B C; Boomsma, D I; van Boheemen, P A; Engesser, L; Kievit, P; Dooijewaard, G; Kluft, C (Thrombosis and Haemostasis, 1995)
A pedigree-based maximum likelihood method developed by Lange et al. (12) was used to study the contribution of a newly defined di-allelic polymorphism in histidine-rich glycoprotein (HRG) to the plasma levels of HRG. In four families (n = 99) and 20 volunteers we found a heritability of 70%, an age effect of 3% and an effect of individual environmental factors of 27%. These results are remarkably similar to the results found in a previous parent-twin study in which a heritability of 69% and an effect of random environment of 31% was found. The overall genetic influence in the present study can be subdivided into an effect of 59% by the HRG phenotype and 11% by residual genetic factors. The influence of the HRG phenotype of 59% can entirely be explained by adding up the effect of the two alleles that make up the phenotype. These results indicate a codominant inheritance pattern of HRG levels in which the genetic influence can almost completely be ascribed to the additive effect of the di-allelic HRG locus whereas only a small part is due to other loci.